Virtual reality for chronic obstructive pulmonary disease: insights from a scoping review - Alabdulmohsen, Dalal M.; Alabdulmohsen, Suha M. (International Journal of Advances in Medicine, 2025)
Recent advances in virtual reality (VR) technology have made it possible to use VR in healthcare settings to improve patient care and rehabilitation, with promising results in various clinical applications. This study aims to review the existing literature exploring the applications and potential benefits of VR for individuals with chronic obstructive pulmonary disease (COPD). A search of six databases, including PubMed, Medline, ScienceDirect, Web of Science, Ebsco, and ProQuest, was conducted to identify different studies exploring various VR applications for COPD patients. The search, updated in November 2024, yielded 2835 results, from which 18 diverse studies on this topic were included. The 18 publications included in the qualitative analysis were published in 2019-2024. These studies included 6 systematic reviews and meta-analyses, 4 mixed-methods studies, 3 observational studies, 3 conference papers, and 2 clinical trials. Among these, 11 studies investigated the efficacy of VR-assisted training in enhancing lung function, exercise endurance, and physical activity levels in COPD patients. Additionally, 7 studies explored the impact of VR on depression, anxiety, and stress levels in patients with COPD. Lastly, 8 studies assessed the acceptability, usability, or feasibility of this technology for COPD patients. In conclusion, the studies revealed that VR interventions led to positive outcomes for COPD patients, improving physiotherapeutic parameters, quality of life, and psychological well-being. Patients found VR programs acceptable and easy to use, increasing motivation and adherence to treatment. Further research is needed to assess VR’s long-term effectiveness in reducing exacerbation and hospitalization rates for compliant COPD patients.